SAE Technical Paper Series 2009
DOI: 10.4271/2009-01-1383
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Real-World Drive Cycles on PHEV Battery Requirements

Abstract: Plug-in hybrid electric vehicles (PHEVs) have the ability to significantly reduce petroleum consumption. Argonne National Laboratory (Argonne), working with the FreedomCAR and Fuels Partnership, helped define the battery requirements for PHEVs.Previous studies demonstrated the impact of the vehicle's characteristics, such as its class, mass, or electrical accessories, on the requirements. However, questions on the impact of drive cycles remain outstanding. In this paper, we evaluate the consequences of sizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The class 6 and 7 school buses, with usage, operational drive/duty cycles have shown the ability to typical capacities of 71 to 84 passengers, were located in the accurately represent vehicle operating information in an states of Washington, New York, and Colorado. Although efficient and streamlined manner well suited to downstream smaller-sized vehicles exist that fall under the vocational analysis [8,9,10,11,12,13,14,15,16,17]. Typically category of school buses, no data was collected or examined consisting of speed and time information, these seemingly associated with this special subset, as vehicles falling within simple pieces of information, when properly understood, this group display operating characteristics dissimilar to their have been used to assess the value of new technology and to larger counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…The class 6 and 7 school buses, with usage, operational drive/duty cycles have shown the ability to typical capacities of 71 to 84 passengers, were located in the accurately represent vehicle operating information in an states of Washington, New York, and Colorado. Although efficient and streamlined manner well suited to downstream smaller-sized vehicles exist that fall under the vocational analysis [8,9,10,11,12,13,14,15,16,17]. Typically category of school buses, no data was collected or examined consisting of speed and time information, these seemingly associated with this special subset, as vehicles falling within simple pieces of information, when properly understood, this group display operating characteristics dissimilar to their have been used to assess the value of new technology and to larger counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Drive cycle has been shown to dramatically impact fuel consumption and emissions production for MD and HD vehicles [16,17,18,19,20,21]. As such, controlled laboratory test procedures representative of real-world operating…”
Section: Development Of a Representative Transientmentioning
confidence: 99%
“…Hence, it is necessary to develop a unique driving cycle for each typical city and region. Moreover, many researchers have found that the energy consumption of an EV for a real-world driving cycle greatly differs from that based on the international standard driving cycles [19,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%